Quantification of Environmental DNA (eDNA) shedding and decay rates for three commercially harvested fish species and comparison between eDNA detection and trawl catches - Anish Kirtane (Wiley, 2021)
Abstract Stock assessments are critical to inform decisions for sustainable fisheries management. Environmental DNA (eDNA) analysis is a potential tool for assessing fish biomass and populations to aid in stock assessments. To facilitate modeling of biomass based on eDNA data, shedding and decay rates are needed. We designed species‐specific, probe‐based qPCR assays for three economically important fish species: black sea bass (Centropristis striata), winter flounder (Pseudopleuronectes americanus), and summer flounder (Paralichthys dentatus). Winter flounder eDNA was measured using two qPCR assays (135 and 292 bp). We report the eDNA shedding and decay rates and the associated variability from two replicate experimental systems. The eDNA decay rates were not significantly different between all species. The eDNA shedding rates between the two replicate systems were significantly different for winter flounder (135 bp assay) and summer flounder. qPCR amplicon length did not affect the eDNA decay rates for winter flounder. The three new qPCR assays were tested in environmental waters alongside traditional trawl surveys. No eDNA from BSB, WF, or SF was detected by eDNA methods, and out of 13 bottom trawls over 6 days only 1 WF, 1 SF, and 2 BSB were caught. This research presents three new, efficient qPCR assays and shows agreement between eDNA methods and trawl surveys suggesting low abundance or absence of target fish.